Design and Implementation of Doctor Scheduling System Using Graph Coloring and Backtracking Approach - Shrivastava, G; Patidar, H (International Journal of Computer Sciences and Engineering, 2019)
The availability of doctors is a major problem that people are facing especially in the rural areas. On the other hand, there are some areas which have large number of doctors than actually required. Because of this uneven distribution of doctors, people in the remote areas remain deprived of medical facilities and are living an unhealthy lifestyle. This paper describes the optimization of schedule of doctors using graph coloring and backtracking approach so that they can be evenly distributed across various locations and the people who are currently not getting proper medical facilities will be able to get treatments on time. This technique serves two purposes, namely, resource optimization and cost optimization. An optimized schedule of doctors will be provided. Only the required number of doctors will be present at a particular location. The remaining doctors will be sent to some other locations. If implemented on a large scale such as in government schemes, this can be a great contribution to the society.